Amiloride resistance in the methanoarcheon Methanothermobacter thermoautotrophicus: characterization of membrane-associated proteins - Surín, S; Cubonová, L'; Majerník, A I; Smigán, P (Folia microbiologica, 2006)
An amiloride-resistant mutant with diminished Na+/H+ antiporter activity was isolated from Methanothermobacter thermoautotrophicus. To define the protein basis of amiloride resistance, the composition of membrane-associated proteins was partially characterized and compared with that of the wild type strain. An abundant 670-kDa membrane-associated protein that was present only in the mutant strain was analyzed by MALDI-TOF MS and identified as a coenzyme F420-reducing hydrogenase. The amiloride resistance was not accompanied by changes in protein size or changes in the level of subunits A or B of the A1A0-type ATP synthase; on the other hand, the SDS-PAGE patterns of the chloroform-methanol extract of membranes from both strains were different. Two bands with calculated molecular mass 16 and 11 kDa were identified as MtrD and AtpK, respectively. The observed over-expression of a 22.7-kDa protein in the mutant cells may represent the multimeric form of the MtrD subunit. These results show that the impairment of the Na+/H+ antiporter system in the amiloride-resistant mutant of Methanothermobacter thermoautotrophicus is accompanied by only small changes in a few membrane-associated proteins.
Keywords: amilorid; Mutant Proteins; elektroforéza v polyakrylamidovém gelu; membránové proteiny; bakteriální léková rezistence; Membrane Proteins; Sodium Channel Blockers; Drug Resistance, Bacterial; Na(+)-H(+) antiport; Amiloride; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Methanobacteriaceae; Bacterial Proteins; Electrophoresis, Polyacrylamide Gel; Sodium-Hydrogen Exchangers; blokátory sodíkových kanálů; spektrometrie hmotnostní - ionizace laserem za účasti matrice; mutantní proteiny; bakteriální proteiny